Assessment Tools for Detecting Malnutrition among Elderly in Shelter Homes: A Systematic Review - Abdul Mutalib, Maisarah; Abdul Kadir, Noor Atiqah Aizan; Shamsuddin, Aida Soraya; Khalid, Khalisanni (IIUM Medical Journal Malaysia, 2024)
Assessing nutritional status in older people is essential to screen for malnutrition and identify the individuals requiring nutritional intervention for a better quality of life and longer life expectancy. This review aimed to investigate malnutrition and the role of nutritional assessment tools among older people in Malaysia. We systematically reviewed the publications from 2000 to 2019 using PubMed/MEDLINE and Scopus databases, recovering 15 original articles published until January 2022. This systematic review was conducted from May to September 2022. Two reviewers were involved in the process of the selection of articles and data extraction. Only research papers on malnutrition among older people in institutionalized settings in Malaysia were included. Four articles related to malnutrition in older people in old folk homes in Malaysia were included in this review. The tools with the most significant evidence were Mini Nutritional Assessment (MNA) and Nutritional Health Checklist (NHC) in residential care for the elderly. It was found that the incidence of malnutrition among the elderly in old folk homes in Malaysia ranged from 12.3% to 17.4%. Meanwhile, 40.4% to 57.7% of the population are documented to be at risk of malnutrition. NA and DETERMINE NHC were found to be most suitable for use in residential care due to their high sensitivity and specificity. A subsequent study is proposed to build and implement a scoring system to rate screening tools based on the validity, suitability, and practicability of the tools to help with malnutrition screening research and clinical practice in Malaysia and internationally.